THE ROLE OF BIG DATA IN TRANSFORMING PUBLIC SERVICES TOWARDS SMART CITY IN SIDOARJO - Rama Gading, Prabu; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the role of Big Data in accelerating the transformation of public services in Sidoarjo Regency toward the Smart City concept. Method: A qualitative research approach was employed, utilizing literature studies and in-depth interviews with officials from the Sidoarjo Central Bureau of Statistics (BPS). Results: The findings reveal that while several digital platforms such as SIPRAJA, SIAK, and e-Health have been implemented, the integration and effective utilization of Big Data remain limited. The challenges identified include data quality inconsistencies, lack of inter-agency system integration, and the absence of a strong data-driven organizational culture. This study further highlights five critical indicators in the Data-Driven Decision Making (DDDM) framework: data quality, analytical capability, decision-making processes, organizational culture, and technological infrastructure. Although infrastructure and analytical tools are in place, their effectiveness is constrained by weak data integration and limited application in public policy formulation. Novelty: This research provides a contextualized analysis of how Big Data adoption in local governance encounters institutional and cultural barriers, offering insights into the necessity of institutional reform, enhanced data literacy, and the development of a robust data ecosystem for achieving smart and responsive governance.